2007
DOI: 10.1017/s0305741007002068
|View full text |Cite
|
Sign up to set email alerts
|

From Resisting to “Embracing?” the One-Child Rule: Understanding New Fertility Trends in a Central China Village

Abstract: From its initiation in 1979, China's one-child policy has been controversial. Most critiques on the stringent birth control policy in rural China still focus on the resistance framework and there is very little research on whether Chinese peasant families are changing their fertility preferences and behaviours when confronting both the state birth control policy and the rapidly changing social and economic environment. Based on recent ethnographic study in a central China village, this article seeks to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…For example, scholars disagree on what are the major driving forces of fertility decline (Cai 2010; Lavely and Freedman 1990; Li, Zhang, and Zhu 2005). Also, results from quantitative analyses based on publicly available data do not entirely match with those from in-depth fieldwork studies in terms of the roles that specific variables (such as education and economic development) play in affecting fertility behaviors (Greenhalgh and Winckler 2005; Harrell et al 2011; Peng 2010; Qian 1997; Short and Zhai 1998; Zhang 1999, 2007). …”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, scholars disagree on what are the major driving forces of fertility decline (Cai 2010; Lavely and Freedman 1990; Li, Zhang, and Zhu 2005). Also, results from quantitative analyses based on publicly available data do not entirely match with those from in-depth fieldwork studies in terms of the roles that specific variables (such as education and economic development) play in affecting fertility behaviors (Greenhalgh and Winckler 2005; Harrell et al 2011; Peng 2010; Qian 1997; Short and Zhai 1998; Zhang 1999, 2007). …”
Section: Introductionmentioning
confidence: 94%
“…As a result, one may observe distinctive fertility behaviors in certain places that differ from general patterns. For example, ethnographic research conducted by Zhang (2007) found a reversal relationship between fertility rates and economic development levels. In areas where the economic development level is high, wealthy families tend to have more children since they are able to pay the fines, while relatively poor rural families tend to have only one child due to the concern of high costs.…”
Section: Background and Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The timing of the surveys is pertinent for the current analysis because peasant resistance to the onechild policy was still at its peak level in the early 1990s. In recent years more and more young rural couples start to embrace the birth control policy and want a smaller family (Zhang 2007).…”
Section: Data Measurement and Methodsmentioning
confidence: 99%